ANALISIS FAKTOR RISIKO TERJADINYA POSTPARTUM BLUES DI RUANG WIJAYA KUSUMA - Qonita; Umalihayati; Vega Muhida (Journal Of Applied Health Research And Development, 2021)
Background During the postpartum period, postpartum mothers will experience physiological, psychological and social adaptations. However, not all postpartum mothers can pass the adaptation to the postpartum period smoothly. Postpartum mothers may experience psychological disorders during childbirth, one of which is anxiety. The incidence of post partum blues around the world is quite high, namely 26-85%. These data show 81% maternal mortality rate (AKI) due to complications during pregnancy and childbirth, and 25% cases of post partum blues. The incidence of post partum blues in Indonesia ranges from 50-70% in post partum mothers Objective To analyze the risk factors that influence the occurrence of postpartum blues in the Wijaya Kusuma Methods: The research design used is a type of analytical study with a cross sectional approach where the dependent variable is postpartum blues and the independent variable is risk factors, such as age, education, employment status, economic status, parity, pregnancy status, type of delivery and social support. husband. The population in this study was 2,408 people and the sample used was 97 respondents with the technique of taking in this study using accidental sampling technique. Result There were 24 postpartum blues (24.7%) of postpartum blues. Primiparous parity has a 6,686 times chance for the occurrence of postpartum blues compared to multiparous parity (OR = 6,686; 95% CI: 1,644-27,184) and husband's social support has less chance of 29,777 times for the occurrence of postpartum blues compared to good husband's social support (OR = 29,777; 95% CI: 2,679-330,941). Meanwhile, the factors that are proven not to be risk factors for the occurrence of postpartum blues are: age, education, employment status, economic status, pregnancy status and type of delivery. Conclusion Husband's social support is the most dominant risk factor contributing to the postpartum blues. Preventive action is needed, such as involving husbands in providing information about maternal and child health, as well as anticipating early detection of postpartum blues with the quality of extracting patient information (anamnesis), so as to reduce the incidence of postpartum blues.